2010
DOI: 10.1097/hjr.0b013e32832e19a3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia at admission in acute coronary syndrome patients: prognostic value in diabetics and non-diabetics

Abstract: This study suggests that, in a broad ACS population, hyperglycaemia at admission is a short-term and long-term bad prognosis marker, particularly in non-diabetic patients, being a strong independent predictor of in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Several studies have demonstrated that acute hyperglycemia is a powerful predictor of mortality, larger infarct size and increased risk of cardiovascular complications in myocardial infarction patients regardless of the diabetic state [30][31][32][33][34][35]. For every 18-mg/ dL increase in glucose level, there is a 4% increase in mortality in nondiabetic patients presenting with myocardial infarction [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that acute hyperglycemia is a powerful predictor of mortality, larger infarct size and increased risk of cardiovascular complications in myocardial infarction patients regardless of the diabetic state [30][31][32][33][34][35]. For every 18-mg/ dL increase in glucose level, there is a 4% increase in mortality in nondiabetic patients presenting with myocardial infarction [36].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In fact, in a broad ACS population, hyperglycaemia at admission is a short-term and long-term prognostic marker. 1 A high glucose level at admission is often attributed to 'stress hyperglycaemia' and might reflect an acute response to the hyperadrenergic state, with catecholamine release and induction of glycogenolysis.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is useful in patients both with and without diabetes. [2][3][4][5][6][7][8][9] It is usually caused by stress hyperglycaemia induced by catecholamines, which, in turn, are correlated with myocardial lesion extension. 1 However, risk scores applied in clinical practice do not include this variable.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate control of glycaemia is advised currently. In the latest ESC guidelines, it is emphasized that insulin should be considered in patients presenting with ACS and with hyperglycemia (> 10 mmol/L or > 180 mg/dL), taking into account the comorbidities [1,21,[24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%